Exchange rate regime in a crisis: The case of Azerbaijan - Samedova, Elnara; Mamedova, Sevda; Aliyeva, Mehriban; Samadova, Mehriban; Kashiyeva, Leman (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This study aims to substantiate the practicality of establishing a fixed exchange rate (FER) under external shocks to the Azerbaijani economy. Using regression analysis, principal component analysis, and the Granger causality test, we substantiated the inexpediency of a fixed FER for the manat (the national currency) due to: the ineffective fiscal and monetary policy of the state, weak integration into the U.S. economy, distrust of the manat in the population, and the weakness of currency hedging. Artificial retention of a FER will lead to devaluation and chronic economic recession (inflation growth, a decrease in real incomes of the population, a reduction of GDP per capita, and an increase in unemployment). It is substantiated that an increase in public confidence in the national currency should become the basis for the transition to a floating exchange rate (FER) for the manat as it will help to get the actual value of the manat.